Hong Point Estimate Method to analyze uncertainty in the underground cables temperature. (January 2021) - Abootorabi Zarchi, Davoud; Vahidi, Behrooz
Highlights: An analytical formula is studied to compute the temperature of underground cables. The Thermal Margin Index (TMI) is introduced and the probability of unreliability is calculated. Obtained simulation results have shown that HPEM requires less input data. Abstract: Due to the uncertainty in parameters such as ambient temperature, soil thermal resistivity, backfill thermal resistivity, current being carried by the cable, the conductor temperature has an inherent uncertainty that can be described by a probability distribution function. For the first time, Hong Point Estimate Method (HPEM) has been used to analyze the uncertainty in the temperature of underground cables in concrete duct banks and pdf of cable temperature is found. In this paper, the simple and fast HPEM has been used to calculate the j'th moment of conductor temperature based on the moments of the probabilistic input variables (j = 1…4). Simulation results from underground cables temperature have been compared to that of Monte Carlo simulations and the First Order Second Moment (FOSM) method and show superior performance with negligible error. To show an implementation of HPEM, for the first time, statistical cable configuration optimization has been studied and simulated by taking into account the uncertainty problem. Depending on the confidence level chosen, the total ampacity of the underground cable in the concrete duct bank is changed. The results show that when the confidence level increases the total ampacity decreases.